The mediating impact of occupational stress on leadership style and job performance - Chew Abdullah, Nor Azimah; Balakrishnan, Thilakavathi (Universiti Teknologi Malaysia, 2016)
The aim of this study is to evaluate the intervening effect of occupational stress on leadership style and job performance. Using a proportionate stratified random sampling, questionnaire survey was employed and distributed to the employees of utility industries in Malaysia and a total of 175 employees participated. The regression results showed that: (1) it is partially supported for a significant association between leadership style and job performance, (2) it is partially supported for a significant association between leadership style and occupational stress. Contrary to expectation, there have no intervening effect of occupational stress on the association between leadership style and job performance. One probable explanation could be that the occupational stress level itself was found low among respondents. Respondents highlighted they have the work-related stress but perhaps due to most of them are healthy, educated, lack in working experience, or due to they are yuppies, (that is indicating they are in young age, ambitious, and hunger for challenging tasks), they did not perceive the stress as the actual stress as felt by the other group of age.Thus, the result suggested that occupational stress as an intervening role among the yuppies group is not a relevant issue in discussing job performance. In future study, other factors should be considered to increase about the explanation on job performance.